PENCEGAHAN STUNTING MELALUI EDUKASI DAN PENDAMPINGAN PEMBUATAN MPASI UNTUK MENINGKATKAN PENGETAHUAN IBU DI DESA JATISARI - Aji Permana, Roby; Dita Dwi Marcelina; Sely Tri Wahyuni; Makhya Al Inayatul Iza; Angga Dwi Kurniawan (LPPM Universitas dr. Soebandi, 2025)
Stunting remains a significant public health challenge, particularly in developing regions. In Jatisari Village, the prevalence of stunting among children under five necessitates targeted interventions to improve nutritional outcomes. This community service initiative addressed this critical issue by focusing on improving maternal knowledge and practices related to complementary feeding. This program aimed to enhance mothers' understanding of stunting prevention and provide practical guidance on preparing nutritious and age-appropriate complementary foods (MPASI) for their infants in Jatisari Village. The activity utilized a two-pronged approach: interactive health education sessions to convey theoretical knowledge about stunting and MPASI, followed by hands-on demonstrations and direct assistance in preparing MPASI. A pre-test and post-test methodology was employed to assess the immediate impact of the intervention on participants' knowledge levels. The comparative analysis of pre-test and post-test scores demonstrated a significant improvement in participants' knowledge regarding stunting prevention and the proper preparation of MPASI. This indicates the effectiveness of the educational and practical intervention in enhancing understanding. The positive shift in knowledge among mothers suggests that targeted educational and practical support can play a crucial role in combating stunting. This intervention is expected to contribute to improved feeding practices and ultimately, better nutritional status and optimal growth for children in Jatisari Village.